Enhancing Critical Language Awareness and Democratic Participation in Social Studies Using a Digital Civic Debate Platform - Mutiani, Mutiani; Jumriani, Jumriani; Ilhami, M. Ridha; Ratumbuysang, Monry Fraick Nicky Gillian; Assyauqi, Mohamad Iqbal; Susilawati, Aay (International Journal of Language Education, 2025)
This study aims to investigate the effectiveness of a digital civic debate platform in enhancing students’ Critical Language Awareness (CLA) and promoting democratic participation in social studies education. Employing a research and development methodology, the study adopts the ADDIE instructional design model, encompassing five systematic phases: analysis, design, development, implementation, and evaluation. The platform developed through this process was tested and implemented among 115 undergraduate students (39 male and 76 female). The results demonstrate that the digital debate platform significantly enhances both students’ critical language awareness and their capacity for democratic engagement. The platform was validated by three experts, deemed feasible for instructional use, and demonstrated strong results in classroom implementation. Students demonstrated marked improvements across all CLA dimensions, including phonological, morphological, syntactic, semantic, communicative, and cultural awareness. The use of digital debate as a pedagogical medium not only facilitated linguistic competence but also fostered inclusive, reflective, and ethically grounded civic discourse. This study provides compelling evidence for the integration of CLA-based digital learning environments in higher education, particularly as a means to cultivate active, critical, and responsible young citizens in the digital era.